Inhibition of the MET Kinase Activity and Cell Growth in MET-Addicted Cancer Cells by Bi-Paratopic Linking. Issue 10 (3rd May 2019) - Andres, Fabio; Iamele, Luisa; Meyer, Timo; Stüber, Jakob C.; Kast, Florian; Gherardi, Ermanno; Niemann, Hartmut H.; Plückthun, Andreas
Abstract: MET, the product of the c-MET proto-oncogene, and its ligand hepatocyte growth factor/scatter factor (HGF/SF) control survival, proliferation and migration during development and tissue regeneration. HGF/SF-MET signaling is equally crucial for growth and metastasis of a variety of human tumors, but resistance to small-molecule inhibitors of MET kinase develops rapidly and therapeutic antibody targeting remains challenging. We made use of the designed ankyrin repeat protein (DARPin) technology to develop an alternative approach for inhibiting MET. We generated a collection of MET-binding DARPins covering epitopes in the extracellular MET domains and created comprehensive sets of bi-paratopic fusion proteins. This new class of molecules efficiently inhibited MET kinase activity and downstream signaling, caused receptor downregulation and strongly inhibited the proliferation of MET-dependent gastric carcinoma cells carrying MET locus amplifications. MET-specific bi-paratopic DARPins may represent a novel and potent strategy for therapeutic targeting of MET and other receptors, and this study has elucidated their mode of action. Graphical Abstract: Unlabelled Image Highlights: DARPins were selected to the different extracellular domains of MET. A comprehensive set of bi-paratopic binders was constructed and analyzed. Several strong MET signaling inhibitors were found, dependent on geometry. A crystal structure of the complex helps explain the mode of action. The molecules downregulate MET and strongly inhibit MET-dependent carcinoma cells.